2016
DOI: 10.1016/j.ymgme.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Prospective exploratory muscle biopsy, imaging, and functional assessment in patients with late-onset Pompe disease treated with alglucosidase alfa: The EMBASSY Study

Abstract: This exploratory study provides novel insights into the histopathologic effects of ERT in late-onset Pompe disease patients. Ultrastructural examination of muscle biopsies demonstrated reduced lysosomal glycogen after ERT. Findings are consistent with stabilization of disease by ERT in treatment-naïve patients with late-onset Pompe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
5
48
0
1
Order By: Relevance
“…These data confirm that early starting ERT allows the best outcomes. A recent study on 16 patients (EMBASSY study) demonstrated a significant reduction in lysosomal glycogen after 6 months of ERT, confirming the stabilization of the disease in ERT-naïve LOPD patients [13]. Formation of anti-rhGAA antibodies is a well known side effect of ERT.…”
Section: Discussionmentioning
confidence: 74%
“…These data confirm that early starting ERT allows the best outcomes. A recent study on 16 patients (EMBASSY study) demonstrated a significant reduction in lysosomal glycogen after 6 months of ERT, confirming the stabilization of the disease in ERT-naïve LOPD patients [13]. Formation of anti-rhGAA antibodies is a well known side effect of ERT.…”
Section: Discussionmentioning
confidence: 74%
“…4 Indeed, the only previous study to demonstrate the clearance of accumulated glycogen in the skeletal muscle of LOPD had enrolled patients naive to ERT. 25 A recent short-term study with a pharmacologic chaperone plus ERT increased GAA activity in muscle without lowering glycogen content in patients with LOPD, demonstrating the need for a sustained effect to achieve biochemical correction. 26 Therefore, this is the first study to demonstrate improved biochemical correction of skeletal muscle in patients with LOPD who were previously treated with ERT.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, glycogen content is generally low in adults with Pompe disease and there is limited longitudinal information regarding glycogen clearance from muscle with enzyme replacement therapy. In the Exploratory Muscle Biopsy Assessment Study (EMBASSY) of alglucosidase alfa in LOPD [21] , quadriceps biopsy glycogen was found both in lysosomes and cytoplasm at baseline (mean 5.3%; range 1.0-14.2%); after 24 weeks' therapy, lysosomal glycogen decreased in 10 patients and increased in 3 patients. Statistically significant changes were noted in 6 patients (4 had decreased glycogen and 2 increased glycogen), while cytoplasmic glycogen remained, and the total area of glycogen showed small reductions from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Response to GAA replacement is determined by the severity of damage at treatment initiation and extent of lysosomal glycogen accumulation [15,20,21] , and by the magnitude of muscle GAA uptake achieved on therapy [22,23] . Alglucosidase alfa is approved worldwide [24,25] for Pompe disease treatment.…”
Section: Introductionmentioning
confidence: 99%